PERLINDUNGAN HUKUM TERHADAP AHLI WARIS ATAS UANG PERTANGGUNGAN ASURANSI JIWA (Studi Kasus Putusan Pengadilan Negeri Lubuk Pakam Nomor : 10/Pdt.G/2015/PN Lbp) - Alusianto Hamonangan; Ria Sintha Devi; Melky Saro Bulyan Zebua (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
Life insurance is an insurance, whereby an insurer binds himself to an insured person, by receiving a premium, to provide reimbursement due to a death event. Study and analyze the heirs whose names do not recommend as beneficiaries in a life insurance policy to which the heirs have responded as heirs. Indication of wishes to the insured party's wishes submitted in the SPAJ and agreed upon in an agreement document called an Insurance Policy. In this study raised the title Legal Protection Against Inheritance Who Is Not Designated in Life Insurance Policy (Study District Court Decision Number: 10 / Pdt.G / 2015 / PN Lbp). The formulation of the problem in this research, first how are the beneficiaries in life insurance after the insured dies (District Court Decision Number: 10 / Pdt.G / 2015 / PN Lbp)? Second, how are the legal efforts of the heirs appointed to get the right to money? life insurance coverage as inheritance (District Court Decision Number: 10 / Pdt.G / 2015 / PN Lbp)?, three, how is the legal protection in the decision that decides the inheritance rights to life insurance coverage money (District Court Decision Number: 10 / Pdt.G / 2015 / PN Lbp)?. This type of research is a normative legal approach method, the nature of this research is descriptive in accordance with the problem and research objectives.The results of the study investigated the consideration that the judge's consideration in making the decision number: 10 / Pdt.G / 2015.PN Lbp, based on several considerations, the judge examined arguments, letters, certificates and decided that the sum insured was an inheritance that the panel of judges ordered and passed guided by arguments, evidence and evidence submitted in the trial. The judge's decision obtains a stipulation regarding the legal heir for the party who wins the case, obtains legal certainty regarding the status of inheritance ownership in the form of compensation from life insurance. As a recipient of life insurance funds, they have an administration because the heirs are actually the heirs regulated in the Civil Code and determined by a judge's decision. The judge's decision obtains a stipulation regarding the legal heir for the winning party in the case, obtains legal certainty regarding the status of inheritance ownership in the form of compensation from life insurance to the legal heir.